Determinants of return migration in Spain in its new role as a receiving country - Gemma Larramona (European Regional Science Association (ERSA), 2011)
Around 5% of the foreign population residing in Spain took the decision to leave this country in 2009. Spain has recently become a receiving country for migrants and the phenomenon of temporary migration is on the rise. The aim of this paper is to provide some insights into the determinants that affect the decision of foreign immigrants to return to their country of birth, once the decision to leave Spain has been taken.
Keywords: 330